Unravelling the dynamics of behavioral loyalty: A model for domestic tourists exploring Terengganu - Ghani, Nur Izzati Ab; Nasir, Muhamad Nasyat Muhamad; Mohamad, Mahadzirah; Muhammad, Norhilmi; Karim, Fazida; Sulaiman, Ruhaizan (Journal of Tourism Management Research, 2024)
This study examines a model for domestic tourists exploring Terengganu. The Terengganu Tourism Department is tasked with increasing tourist numbers, enhancing their expenditures through heightened allure and superior services, creating an indelible experiential milieu, and establishing Terengganu as a prominent destination. However, recent statistics depict Terengganu as experiencing a diminutive influx of domestic tourists and corresponding tourism receipts compared to other states. In 2018, Terengganu ranked ninth in domestic tourist visitations and associated receipts. Hence, this study aims to ascertain the determinants influencing behavioral loyalty among domestic tourists towards Kuala Terengganu. Data collection transpired through an online questionnaire deployed via Google Forms, synchronized with the global advent of COVID-19, which precipitated ramifications across nations. Respondents included domestic tourists visiting Kuala Terengganu. Data analysis involved 201 respondents, using structural equation modeling. The empirical findings describe that the attractiveness of the destination substantiates a discernible impact on tourist satisfaction. Furthermore, the outcomes highlight that tourist satisfaction exerts a noteworthy influence on eWord-of-mouth (eWOM) and behavioral loyalty. The findings indicate that tourist satisfaction comprehensively mediates the relationship between destination attractiveness and both eWOM and behavioral loyalty. It asserts that Kuala Terengganu’s distinctiveness from competing Malaysian destinations is facilitated by destination attractiveness, involving recreational amenities, leisure facilities, infrastructural attributes, and overall appeal. Consequently, proficient promotional strategies can be devised by Tourism Terengganu, accentuating the advantageous and captivating features of Kuala Terengganu’s attractions. These aspects are strategically tailored to resonate with the cognitive and emotional assessments of domestic tourists, instigating a proclivity to recurrently choose Kuala Terengganu as their preferred travel destination.